Imaginaire et différ(a)nce : générateurs de paysages - Rita Occhiuto (Projets de Paysage)
This article reflects on the need to restore confidence in the ability of the professions engaged in observing and designing the landscape to prefigure and reinvent landscapes by using imagination among other things, and on the need to recognise the ability to master the tools for representing reality in landscape design. Imagination, combined with the aptitude for detailed observation, is based on the capacity to read, understand and interpret the geographic forms and their continuous transformations due to the actions of nature and man (European Landscape Convention). Expressed in the forms of lines, outlines and incisions, this action marks sites, like a form of writing requiring a physical and mental engagement in situ. Thus emerge narratives and experiences producing images/drawings which convey characters, languages and tensions and constitute the creative and innovative force of landscape projects which consider what exists as a field of forces in action – therefore a territory in movement. Our assumption is that the project produces a different or deferred meaning, a différ(a)nce, a textual composition with a double structure : "trace-gap", "residual and dynamic", "retentive and subject to propensity", (Jacques Derrida), linked to the past (trace) and projecting into the future through a distance or distancing (gap).